Relationships Between Teacher Feedback and Student Motivation: A Comparison Between Male and Female Students - Guo, Wenjuan; Zhou, Wenye (Frontiers in Psychology, 2021)
his study aimed to investigate gender differences in teacher feedback, students’ motivation and their relationship patterns in the context of first language learning. In total, 1,082 secondary students in China (538 male and 544 female students) participated in this study. The results of MANOVAs suggested that language teachers provided less directive feedback but more criticism to male than to female students. Male students reported less intrinsic motivation, extrinsic motivation and test anxiety in first language learning than female students. The results of two-group structural equation modelling indicated that both male and female student motivation was best predicted by teachers’ scaffolding feedback and praise. Verification feedback had a negative correlation with female students’ extrinsic motivation and no significant correlation with male students’ motivation. Directive feedback had a negative correlation with male students’ intrinsic motivation and a positive correlation with female students’ extrinsic motivation. Further, teacher criticism only had a negative correlation with female students’ intrinsic motivation. Implications for future research as well as suggestions for language teachers on how to improve male and female students’ motivation are discussed.